Qualidade de vida profissional de atendentes de central de telecomunicações - Parise, Janaina Amoriele (2014)
Technological innovations related to the Internet have caused the restructuring of the telecommunications industry and resulted in an exhausting pace of work and illness among workers from different Telecommunications and Computing sectors. Thus, the professional quality of life of call center workers needs to be studied carefully. Objective: To assess the professional quality of life of call center workers, according to socio-demographic characteristics and problems in the labor process. Methods: This is a descriptive, exploratory, quantitative study conducted with call center workers of a telecommunications company in Sao Jose do Rio Preto, SP. This study was approved by the Ethics Committee for Research on Human Subjects. We used two questionnaires: a socio-demographic questionnaire and the Brazilian validated version of the Professional Quality of Life Questionnaire (ProQoL-35). Results:Workers's socio-demographic characteristics: 80.2% were female; 66.3% were single; up to high school education; mean age 28 years; for 92.9% it was their only job; mean time of work in the company was 3 years; 6-hour work days. Positive PQoL factors reported: Intrinsic motivation, training, available resources and social support. Negative PQoL factors reported: workload and (perceived) organizational support. Conclusion: The results of this study reveal the factors that most affect the professional quality of life in the company studied and contribute to the implementation of actions by occupational health nurses to reduce illness among workers and increase productivity for the company.